Recent Progress in Palladium-Catalyzed Cascade Cyclizations for Natural Product Synthesis - Ohno, Hiroaki; Inuki, Shinsuke (Synthesis, 2018)
Cascade reactions (also represented as domino reactions) realize the step-economical direct construction of natural product core structures. The use of atom-economical elementary reactions in cascade processes can minimize waste production and avoid prefunctionalization of the substrates. Palladium catalysis, which promotes a variety of atom-economical elementary reactions, has long been used as a powerful approach to the direct formation of complex heterocycles. In this short review, palladium-catalyzed cascade reactions for the construction of core structures of natural products reported in the last decade are highlighted.1 Introduction2 Reactions Terminated with Heteronucleophiles2.1 Termination with Nitrogen Nucleophiles2.2 Termination with Oxygen Nucleophiles3 Reactions Terminated with Carbon Functional Groups3.1 Termination with Carbon Nucleophiles3.2 Termination with Heck-Type Reactions4 Conclusion
Keywords: cascade reaction; domino reaction; palladium catalysis; natural product synthesis; step economy